2017
DOI: 10.1007/s00122-017-3032-z
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine treatment and TaPBF-D over-expression increases glutenin accumulation within the wheat grain by hypomethylating the Glu-1 promoters

Abstract: 5-azaC treatment and TaPBF - D over-expression decrease C-methylation status of three Glu - 1 gene promoters, and aid in enhancing the expression of the Glu - 1 genes. The wheat glutenins exert a strong influence over dough elasticity, but the regulation of their encoding genes has not been firmly established. Following treatment with 5-azacytidine (5-azaC), both the weight and glutenin content of the developing and mature grains were significantly increased. The abundance of transcript produced by the Glu-1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…TaSPA-B and TaPBF-D have been identified to regulate wheat glutenin gene, and their homologs in maize (O2 and PBF) show stimulatory and additive effects on maize zein and wheat glutenin genes [14,34,38]. In our results, ω-1,2 gliadin gene and TaPBF showed a little reduction in TaSPA-B OE-3 lines compared with WT ( Figure 5, Table 2).…”
Section: Dual-luciferase Reporter Assay Of the ω-12 Gliadin Gene Prosupporting
confidence: 52%
See 3 more Smart Citations
“…TaSPA-B and TaPBF-D have been identified to regulate wheat glutenin gene, and their homologs in maize (O2 and PBF) show stimulatory and additive effects on maize zein and wheat glutenin genes [14,34,38]. In our results, ω-1,2 gliadin gene and TaPBF showed a little reduction in TaSPA-B OE-3 lines compared with WT ( Figure 5, Table 2).…”
Section: Dual-luciferase Reporter Assay Of the ω-12 Gliadin Gene Prosupporting
confidence: 52%
“…Consistent with these results, TaPBF was reduced in TaSPA-B OE-3 lines (Table 2). TaPBF activated glutenin genes by regulating methylation of the promoter [34]. Our DLR assay revealed that TaSPA-B and TaPBF-D could activate the expression of ω-1,2 gliadin gene, and TaPBF-D showed a higher activation than TaSPA-B ( Figure 7B).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…One alternative to the generation of epigenetic mutants is the use of drugs interfering with epigenetic pathways. Inhibitors of DNA methylases, such as 5-Azacytidine and Zebularine, have been successfully used to induce DNA demethylation in plants (Griffin, Niederhuth, & Schmitz, 2016;Pecinka & Liu, 2014), including crops (Sano, Kamada, Youssefian, Katsumi, & Wabiko, 1990;Santos et al, 2002;Zhu et al, 2018). Although most of hypomethylation and transcriptional changes induced by these drugs are only transient (Baubec, Pecinka, Rozhon, & Mittelsten Scheid, 2009), transgenerational effects have been observed in rice treated with 5-Azacytidine (Sano et al, 1990).…”
Section: Challenges With Cropsmentioning
confidence: 99%